Closed genome sequence of phytopathogen biocontrol agent bacillus velezensis strain AGVL-005, isolated from soybean - Pylro, Victor Satler; Dias, Armando Cavalcante Franco; Andreote, Fernando Dini; Morais, Daniel Kumazawa; de Mello Varani, Alessandro [UNESP]; Andreote, Cristiane Cipolla Fasanella; de Almeida Bernardo, Eduardo Roberto; Zucchi, Tiago (My University, 2018)
We report here the closed and near-complete genome sequence and annotation of Bacillus velezensis strain AGVL-005, a bacterium isolated from soybean seeds in Brazil and used for phytopathogen biocontrol.